Hemp-Derived Hierarchical Porous Carbon with an Optimized Pore Structure by NaOH Activation for Supercapacitor Applications - Khemjiranee Bowornthommatadsana; Kanisorn Klangvijit; Teerayut Uwanno; Mayuree Phonyiem Reilly; Visittapong Yordsri; Weerawut Chaiwat; Satoshi Ichikawa; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Winadda Wongwiriyapan; Morinobu Endo (ACS Omega, 2025)
electrolyte. When assembled into a coin cell with an organic electrolyte, Hurd-4 exhibited a maximum specific capacitance of 39 F/g, a maximum energy density of 34 Wh/kg, and a power density of 395 W/kg, surpassing commercial activated carbon. Additionally, the device maintained 78% capacitance retention after 10,000 cycles at a current density of 0.5 A/g. The superior electrochemical properties are attributed to the largest specific surface area, highest pore volume, and optimal mesopore volume ratio. These results demonstrate the potential of hemp hurd as a highly efficient precursor for synthesizing activated carbon for high-performance supercapacitors.
Keywords: Supercapacitor Materials and Fabrication; Adsorption and biosorption for pollutant removal; Mesoporous Materials and Catalysis